The Role of Brain-Derived Neurotrophic Factor in Comorbid Depression: Possible Linkage with Steroid Hormones, Cytokines, and Nutrition - Numakawa, Tadahiro; Richards, Misty; Nakajima, Shingo; Adachi, Naoki; Furuta, Miyako; Odaka, Haruki; Kunugi, Hiroshi (Frontiers in Psychiatry, 2014)
Increasing evidence demonstrates a connection between growth factor function (including brain-derived neurotrophic factor, BDNF), glucocorticoid levels (one of the steroid hormones), and the pathophysiology of depressive disorders. Because both BDNF and glucocorticoids regulate synaptic function in the central nervous system, their functional interaction is of major concern. Interestingly, alterations in levels of estrogen, another steroid hormone, may play a role in depressive-like behavior in postpartum females with fluctuations of BDNF-related molecules in the brain. BDNF and cytokines, which are protein regulators of inflammation, stimulate multiple intracellular signaling cascades involved in neuropsychiatric illness. Pro-inflammatory cytokines may increase vulnerability to depressive symptoms, such as the increased risk observed in patients with cancer and/or autoimmune diseases. In this review, we discuss the possible relationship between inflammation and depression, in addition to the crosstalk among cytokines, BDNF and steroids. Further, since nutritional status has been shown to affect critical pathways involved in depression through both BDNF function and the monoamine system, we also review current evidence surrounding diet and supplementation (e.g., flavonoids) on BDNF-mediated brain functions.